Pelestarian Seni Budaya melalui Grup Karawitan Putri Kartika Laras di Desa Salamrejo Kabupaten Kulon Progo - Nadilla Sekar Thalenta Kirana (Abdi Seni, 2022)
This article attempts to provide documentation of the P3WILSEN community service program that the Department of Karawitan ISI Yogyakarta’s students and lecturers have conducted. The project area especially targets the female musical ensemble Kartika Laras in Salamrejo Village, Kulon Progo Regency. The existence of this musical ensemble has been greatly impacted by the COVID-19 pandemic condition. Thus, the service program aims to support this art group so they can continue their activities. Within the project, the team implemented several activities including: sharing knowledge on how to work on cengkok ricikan, providing tips related to sindenan knowledge, enhancing the ideal gamelan technique, as well as arranging art performances.